PEMBINAAN USAHA KECIL MENENGAH (UKM) BAKERY MELALUI PENINGKATAN KUALITAS PRODUK, PEMASARAN DIGITAL, DAN PENGELOLAAN USAHA - Benny Cuaca; Bambang Widjanarko Susilo; Edy Susanto; Ayu Miranti Kusumaningrum; Rezky Eko Prasetyo (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Small and Medium Enterprises (SMEs) bakery is one of the business sectors that has quite good prospects in supporting the community's economic growth. The high demand for various bakery products, cakes, and snacks has encouraged the emergence of many small and medium-scale bakery businesses. However, most bakery SMEs still face various obstacles, such as limited ability to manage their business, low use of digital technology for marketing, lack of optimal financial management, and the lack of implementation of good and consistent production standards. This condition has the potential to hinder business development and reduce product competitiveness in the midst of increasingly fierce market competition. Seeing these conditions, Benny Cuaca and the community service team carried out a bakery SME coaching program which aims to increase the capacity of business actors through training and mentoring in aspects of business management, product quality improvement, packaging development, and digital marketing. Coaching activities are carried out through a participatory approach that actively involves business actors in each stage of activities. Through this program, it is hoped that bakery SMEs will be able to improve the quality of their products, expand their marketing reach, and manage their businesses in a more professional and sustainable manner.